Genomic insights into the specialisation and selection of the Jinding duck - H. Chen; Y. Huang; J. Xue; K. luo; H. Tang; S. Zheng; Y. Xiong; Y. Wu; J. Li; R. Xuan; R. Xiong; Y. Gong; et al. (Animal)
The domestication of ducks represents a pivotal evolutionary shift from the unguided propagation of wild species to deliberate human-mediated selection, culminating in distinct behavioural, morphological, and physiological traits that differentiate domesticated ducks from their wild counterparts. This transition has yielded breeds with traits fine-tuned to specific economic roles, such as egg production, meat yield, or dual-purpose functionality. Duck domestication plays a significant role in poultry production globally, meeting the growing demand for eggs and meat in various regions. Here, we focus on the Jinding Duck (JDD), a breed renowned for its prolific egg-laying traits. Employing whole-genome resequencing data from 325 individuals across five Chinese indigenous duck breeds, we aimed to dissect the unique population structure and assess the genetic diversity within the JDD cohort. The findings reveal the distinct genetic heritage of JDD, diverged from other domesticated breeds, and show a relative paucity of genetic diversity. A salient discovery was a 200 kb genomic interval containing three genes (NCF2, SMG7, and ARPC5) with almost exclusive haplotypes, which were inherited from Anas platyrhynchos or Anas zonorhyncha, impacting the morphological attributes of JDD. The study highlights a c.28G>A non−synonymous mutation in the first exon of the LAMC1 gene, which is potentially influencing feather morphology in JDD. Our findings suggest that unique blue eggshell colouration in JDD is likely attributable to variations within the promoter element of the ABCG2 gene, distinguishing it from other breeds. Moreover, the MAP7 and FHL1 genes emerge as significant factors in the laying performance of JDD. These genetic insights are not only crucial for improving the JDD breed but also provide valuable information that could be applied to duck breeding programmes worldwide, helping enhance productivity and meet international demands for high-efficiency poultry breeds.